Unexpected Death Due to Rickettsiosis: Medical-legal and Epidemiological Implications (2017)
Purpose: To present a case of unexpected death due to rickettsiosis and its medical-legal and epidemiological implications. Themes: Acute infections, unexpected death, lawsuit for medical malpractice, and epidemiological consequences of the diagnosis of infectious disease. Elaboration: This article refers to the case of a teenager, resident of Panama City, who had a lethal acute clinical infection. At the time of necropsy, there was no diagnosis to confirm that it was a case of rickettsiosis. Conclusions: Cases of rickettsiosis are not frequent; it is possible that they are not diagnosed in a timely manner, and therefore, they put the population at epidemiological risk. The complexity and promptness of clinical manifestations may cause diagnostic and treatment errors, for which the results of the necropsy are crucial to certify the cause of death and resolve claims for medical malpractice.